Epidemiologic relationship between periodontitis and type 2 diabetes mellitus - Chen-zhou Wu; Yi-hang Yuan; Hang-hang Liu; Shen-sui Li; Bo-wen Zhang; Wen Chen; Zi-jian An; Si-yu Chen; Yong-zhi Wu; Bo Han; Chun-jie Li; Long-jiang Li (BMC, 2020)
Abstract Background To systematically review the epidemiologic relationship between periodontitis and type 2 diabetes mellitus (T2DM). Methods Four electronic databases were searched up until December 2018. The manual search included the reference lists of the included studies and relevant journals. Observational studies evaluating the relationship between T2DM and periodontitis were included. Meta-analyses were conducted using STATA. Results A total of 53 observational studies were included. The Adjusted T2DM prevalence was significantly higher in periodontitis patients (OR = 4.04, p = 0.000), and vice versa (OR = 1.58, p = 0.000). T2DM patients had significantly worse periodontal status, as reflected in a 0.61 mm deeper periodontal pocket, a 0.89 mm higher attachment loss and approximately 2 more lost teeth (all p = 0.000), than those without T2DM. The results of the cohort studies found that T2DM could elevate the risk of developing periodontitis by 34% (p = 0.002). The glycemic control of T2DM patients might result in different periodontitis outcomes. Severe periodontitis increased the incidence of T2DM by 53% (p = 0.000), and this result was stable. In contrast, the impact of mild periodontitis on T2DM incidence (RR = 1.28, p = 0.007) was less robust. Conclusions There is an evident bidirectional relationship between T2DM and periodontitis. Further well-designed cohort studies are needed to confirm this finding. Our results suggest that both dentists and physicians need to be aware of the strong connection between periodontitis and T2DM. Controlling these two diseases might help prevent each other's incidence.